Gustave Doré - Dante Alighieri - InferNo - Plate 9 (Canto III - Charon) - Gustave Doré (Wikimedia Commons, 1857)
Notice iconographique issue de Wikimedia Commons. Titre: Gustave Doré - Dante Alighieri - InferNo - Plate 9 (Canto III - Charon). Gustave Doré 's illustration to Dante's Inferno. Plate IX: Canto III: Arrival of Charon. "And lo! towards us coming in a boat / An old man, hoary with the hair of eld, / Crying: 'Woe unto you, ye souls depraved!'" (Longfellow's translation) "And, lo! toward us in a bark / Comes an old man, hoary white with eld, / Crying "Woe to you, wicked spirits!" (Cary 's translation)
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; Patrimoine; Wikimedia Commons